Evaluation of service quality, clinic image and patient satisfaction facilities (study in Dr Ginting. Sp.B clinic) - Heidemans, Anita Ningrum; Mufti, Digor; Edwar, Rizka Cintya (LLDIKTI Wilayah 1 Sumatera Utara, 2023)
This research aims to determine the influence of service quality, clinic image and facilities on patient satisfaction at Kliik dr. Blonde. This research uses a quantitative descriptive research method. Data collection techniques used questionnaires and documentation about patients seeking treatment or hospitalization at Dr. Ginting Clinic. A total of 40 respondents used simple random sampling techniques. This research uses SPSS application program version 20. The research results show that the variables Service Quality, Clinic Image and Facilities have a positive and significant effect on patient satisfaction. The results of this research can be used as reference material and increase the understanding of other researchers in the field of management, especially in the field of customer satisfaction that is influenced by service quality, brand image and availability of facilities.